2011
DOI: 10.1371/journal.pone.0018232
|View full text |Cite
|
Sign up to set email alerts
|

Association of MiR-126 with Soluble Mesothelin-Related Peptides, a Marker for Malignant Mesothelioma

Abstract: BackgroundImproved detection methods for diagnosis of malignant pleural mesothelioma (MPM) are essential for early and reliable detection as well as treatment. Since recent data point to abnormal levels of microRNAs (miRNAs) in tumors, we hypothesized that a profile of deregulated miRNAs may be a marker of MPM and that the levels of specific miRNAs may be used for monitoring its progress.Methods and ResultsmiRNAs isolated from fresh-frozen biopsies of MPM patients were tested for the expression of 88 types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 44 publications
5
112
2
Order By: Relevance
“…The expression level of miR-126 in the patient serum was found to be associated with soluble mesothelin-related peptides, which are a specific marker of malignant pleural mesothelioma (MPM). miR-126 expression was correlated with a high risk of developing MPM and may be used as a marker for the early detection of MPM (36). This study identified miR-143 and -195 as potentially useful biomarkers in human gastric cancer, due to their similar performance in the clinicopathological factor analysis.…”
Section: Discussionmentioning
confidence: 75%
“…The expression level of miR-126 in the patient serum was found to be associated with soluble mesothelin-related peptides, which are a specific marker of malignant pleural mesothelioma (MPM). miR-126 expression was correlated with a high risk of developing MPM and may be used as a marker for the early detection of MPM (36). This study identified miR-143 and -195 as potentially useful biomarkers in human gastric cancer, due to their similar performance in the clinicopathological factor analysis.…”
Section: Discussionmentioning
confidence: 75%
“…Preliminary analysis evidence miRNAs as possible markers for diagnosis and prognosis of MPM, and hypothesize new mechanisms for the therapy of this malignancy (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Santarelli et al proposed miR-126 as useful marker because significantly remained down-regulated in the malignant tissues compared with the normal tissues (38) and in serum (41) while Kirschner et al confirmed the potential of miR-29c and miR-92a as candidate tumor markers and revealed that miR-625-3p was a promising novel diagnostic marker for MPM (39).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although, gene expression profiling has reached a plateau in this regard, recent miRNA studies illustrate great promise whereas aberrant miRNA profiling and or abnormal miRNA levels in tissues or in plasma can perform as a robust predictor of overall survival and disease outcome in various disorders. Because numerous miRNAs are expressed in a tissue-specific manner and their levels in different organs vary in association with disease states, these small molecules represent an attractive new class of highly specific biomarkers [153][154][155][156][157]. Some reports have previously illustrated the potential of these small RNA molecules as biomarkers in cancerous patients [158].…”
Section: Diagnostic and Prognostic Value Of Mirna: As Novel Promisingmentioning
confidence: 99%